ANALISIS PENGARUH PERUBAHAN TATA GUNA LAHAN MENGGUNAKAN EPA-SWMM DI DAS KRUKUT - Firmansyah, Arief; Kurniyaningrum, Endah; Herlina, Liana; Misshuari, Imas Wihdah; Amin, Rais (Universitas Trisakti, 2024)
Flooding in Jakarta, a lowland area traversed by several rivers, has become a recurring challenge due to increased development, business activities, and land-use changes. This study aims to calculate the design flood discharge for various return periods and analyze the impact of land-use changes on flooding in the Krukut River Basin. The analysis utilized ArcGIS for land-use changes and EPA-SWMM for hydrological and hydraulic simulations. Results indicate that changes in land cover have led to an increase in flood discharge, for instance, in the 2-year return period from 106.01 m³/s (2006) to 108.25 m³/s (2017), and in the 100-year return period from 204.61 m³/s (2006) to 208.93 m³/s (2017). Mitigation efforts, such as the implementation of infiltration wells, were effective in reducing flood discharge, with EPA-SWMM simulations showing a reduction in the 100-year return period from 208.93 m³/s to 186.22 m³/s. This study recommends the implementation of infiltration wells and the enforcement of spatial planning regulations (RTRW) as conservation strategies to mitigate flood risks in the Krukut River Basin.